A mimicking technique of back pressure in the hardware-in-the-loop simulation of a fuel control unit. (April 2020) - Yuan, Yuan; Zhao, Zhiwen; Zhang, Tianhong
In the hardware-in-the-loop (HIL) simulation of the fuel control unit (FCU) for aero-engines, the back pressure has a great impact on the metered fuel, thus influencing the confidence of the simulation. During the practical working process of an aero-engine, the back pressure of the FCU is influenced by the combined effect of the pressure of the combustion chamber, the resistance of the spray nozzles, and the resistance of the distribution valve. There is a need to study the the mimicking technique of FCU back pressure. This paper models the fuel system of an aero-engine so as to reveal the impact of FCU back pressure on the metered fuel and come up with a scheme to calculate the equivalent FCU back pressure. After analyzing the requirements for mimicking the pressure, an automatic regulating facility is designed to adjust the FCU back pressure in real time. Finally, experiments are carried out to verify its performance. Results show that the mimicking technique of back pressure is well suited for application in HIL simulation. It is able to increase the confidence of the simulation and provide guidance to the implementation of mimicking the FCU back pressure.